Leksykon roslin leczniczych - Ruminska, Antonina; Ozarowski, Aleksander (Warszawa : Panstwowe Wydawnictwo Rolnicze i Lesne, 1990)
A dictionary of medicinal herbs.
Includes bibliographical references (p. [542]) and index.
Keywords: Medicinal plants -- Dictionaries